10.1146/annurev-nutr-072610-145121 (CrossRef Listing of Deleted DOIs, 2000)
Body shape influences risk of cardio-metabolic diseases, independent of obesity. An apple shape, defined by larger waist circumference, is associated with higher risk. Higher amounts of visceral and/or subcutaneous adipose tissues contribute to whole-body metabolic risk. In contrast, a pear shape, with higher fat storage in gluteal-femoral depots, exerts protective effects on metabolic health, independent of sex and total adiposity. Differences in growth, remodeling, metabolism, and endocrine functions of adipose depots contribute to these associations. Innervation, blood supply, and sensitivity to endocrine signals and local secreted factors contribute to depot variations in function. At the systemic level, adipose tissues influence metabolic health by secreting adipokines and other factors packaged in extracellular vesicles. Depot differences in the production of secreted factors and their contributions to risk for developing obesity-related metabolic diseases hold promise for understanding the role of body shape in metabolic health.